2022
DOI: 10.3390/plants11050668
|View full text |Cite
|
Sign up to set email alerts
|

MdMADS6 Recruits Histone Deacetylase MdHDA19 to Repress the Expression of the Carotenoid Synthesis-Related Gene MdCCD1 during Fruit Ripening

Abstract: Fruit ripening is regulated by epigenetic modifications and transcription factors, which may function independently or as protein complexes. Our previous study showed that the apple histone deacetylase19 (MdHDA19) suppresses fruit ripening through the deacetylation of histones in related genes. Here, a MADS-box transcription factor (MdMADS6) was identified using a yeast two-hybrid (Y2H) assay as a candidate protein that interacts with MdHDA19 during apple fruit ripening. Furthermore, Y2H, bimolecular fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…MdHDA19, promoting H3k9 deacetylation, can form a MdERF4–dTPL4 complex repressing the expression of MdACS3a gene, specifically active in the early maturation phase. MdHDA19 was furthermore found to interact with MdMADS6, which in turn promoted carotenoid accumulation in apple fruit ( Q. Li et al ., 2022 ).…”
Section: Transcriptional Regulation Of Fruit Ripening In Applementioning
confidence: 99%
“…MdHDA19, promoting H3k9 deacetylation, can form a MdERF4–dTPL4 complex repressing the expression of MdACS3a gene, specifically active in the early maturation phase. MdHDA19 was furthermore found to interact with MdMADS6, which in turn promoted carotenoid accumulation in apple fruit ( Q. Li et al ., 2022 ).…”
Section: Transcriptional Regulation Of Fruit Ripening In Applementioning
confidence: 99%
“…Recently, multiple MADS transcription factors, such as SlRIN, SlCMB1, and SlTAGL1 in tomato, CsMADS3/5/6 in citrus, ,, and AcMADS32 in kiwifruit, could positively regulate carotenoid metabolism; in contrast, some MADS transcription factors, such as tomato SlMADS1, SlFYFL, and SlMBP8 as well as apple MdMADS6, could negatively regulate carotenoid accumulation during fruit ripening. In citrus fruits, CsMADS6 activated the transcription of PSY , PDS , and CCD1 genes by directly binding to their promoters .…”
Section: Regulation Of Carotenoid Biosynthesis By Regulators In Plant...mentioning
confidence: 99%
“…MADS, which is named after the first letters of the four transcription factors first identified in this family, mini chromosome maintenance 1 (MCM1) from Saccharomyces cerevisiae, agamous (AG) from Arabidopsis, deficiens (DEF) from Antirrhinum majus, as well as human serum response factor (SRF), 46 is a transcription factor family extensively involved in the regulation of carotenoid metabolism (Table 2 recognizing and binding the CArG-box (CC-A-rich-GG, also known as MADS-box) of the target gene promoter. 47 Recently, multiple MADS transcription factors, such as SlRIN, SlCMB1, and SlTAGL1 in tomato, 48−50 CsMADS3/5/ 6 in citrus, 13,51,52 and AcMADS32 in kiwifruit, 53 could positively regulate carotenoid metabolism; in contrast, some MADS transcription factors, such as tomato SlMADS1, SlFYFL, and SlMBP8 54−56 as well as apple MdMADS6, 57 could negatively regulate carotenoid accumulation during fruit ripening. In citrus fruits, CsMADS6 activated the transcription of PSY, PDS, and CCD1 genes by directly binding to their promoters.…”
Section: Regulation Of Carotenoid Biosynthesis By Regulators In Plant...mentioning
confidence: 99%
“…Apart from their involvement in flower organ development and other processes, these genes also play a vital role in regulating substance metabolism in plants. For instance, CsMADS6 ( AGAMOUS -like subfamily) in citrus, MdMADS6 from apple, and CaMADS-RIN ( SEP subfamily) in pepper have been found to have significant regulatory roles in the carotenoid synthesis pathway ( Dong et al., 2014 ; Lu et al., 2018 ; Li et al., 2022 ). It has been reported that PfMADS genes may be involved in the flavonoid synthesis pathway of P. frutescens ( Jiang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%